2015
DOI: 10.1519/jsc.0000000000000744
|View full text |Cite
|
Sign up to set email alerts
|

Postactivation Potentiation Enhances Swim Performance in Collegiate Swimmers

Abstract: This study examined postactivation potentiation (PAP) and its effect on performance during sprint swimming. After maximal muscular contraction, the muscles are in both a potentiated and fatigued state. However, fatigue dissipates faster than potentiation, creating a window of opportunity for possible performance enhancement. We observed 30 collegiate swimmers (15 men and 15 women) performing 2 swim trials in a randomized order. The control trial involved a standard swim warm-up, followed by a 6-minute rest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(102 citation statements)
references
References 22 publications
5
82
0
15
Order By: Relevance
“…In recent years, post activation potentiation has been a popular area of research to understand whether this theory has effects on athletes' performance or not. (Hancock et al, 2015;Kilduff et al, 2007;Kilduff et al, 2011;Sandra, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, post activation potentiation has been a popular area of research to understand whether this theory has effects on athletes' performance or not. (Hancock et al, 2015;Kilduff et al, 2007;Kilduff et al, 2011;Sandra, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, squat [13][14][15] , jump [16][17][18] and sprint 16,19,20 protocols stand out. In all of these studies, significant performance differences after potentiation protocol were found (p <0.05).…”
Section: Introductionmentioning
confidence: 99%
“…In freestyle swimming, the upper limbs are responsible for about 90% of the total workout (Deschodt et al, 1999). At least in adult swimmers, there is a strong relationship between the strength and power of the upper limbs and the sprinting performance (Hancock et al, 2014;Hawley et al, 1992). The swimmers in cluster 1 ("talented") were characterized not only by high kinematics (swimming velocity and stroke index) but also by a high throwing velocity (S&C).…”
Section: Discussionmentioning
confidence: 99%